A representation of Malaysian Malay women identity from a systemic functional perspective - Swee, Mee Tan; Joanna Tjin Ai Tan,; Gerard Segaya Raj, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Employing a systemic functional analysis of two selected stories written by two different Malay women writers, namely Dina Zaman and Karina Bahrin, this paper investigates the perception of Malay women from two contrasting settings, the metropolitan Kuala Lumpur and a kampong in Terengganu. The study explores the social cultural identity of Malay women within a linguistic context based on an analysis of thematic choice derived from the Hallidayan notion of grammar. In And She Became an Angel (Dina Zaman), suggesting a subordinated female identity in a Malay kampong context, findings derived from the clausal analysis concluded that the main protagonist, Mandak successfully transcended herself from a victimized role into a heroin at the end of the story. She eventually had become an angel in a fire to embrace the only one thing of her life. However, in A Subtle Degree of Restraint (Karina Bahrin), Elena and Badariah, the two representations of new Malay women living in the cosmopolitan Kuala Lumpur, encountered subtle feelings of deprivation in their contrasting life conditions through either marriage or barrenness. Applying a Hallidayan framework that looks at thematic choice in the system of Theme and Rheme and the System of Transitivity, this paper justifies its findings from the distribution and the experiential elements of thematic choices in the two short stories from a linguistic spectrum. It also signifies a refreshing approach on literary studies in the MLE.